2021
DOI: 10.3390/met11040672
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Direct Laser Deposition of a Martensitic Steel Powder (Metco 42C) on 42CrMo4 Steel

Abstract: In this study, the deposition of martensitic stainless-steel (Metco 42C) powder on 42CrMo4 structural steel by direct laser deposition (DLD) was investigated. Clads were produced by varying the laser power, scanning speed, feed rate, and preheating. The effect of these processing variables on the microstructure and microhardness of the clads was analyzed, as well as their soundness, yield (measured by dilution), and geometric characteristics (height, width, and depth). The complex interaction of the evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In the meantime, the substrate material functions as a cooling media, consequently, microstructure changes in comparison with that of the virgin substrate, forming HAZ. Recent studies showed that the HAZ properties depended on the temperature of the substrate, in the room temperature or heated up to 250 °C [ 26 , 27 , 28 ]. The substrate used in the current study is AISI 1045 that is susceptible to martensitic transformation, depending on the cooling rate [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the meantime, the substrate material functions as a cooling media, consequently, microstructure changes in comparison with that of the virgin substrate, forming HAZ. Recent studies showed that the HAZ properties depended on the temperature of the substrate, in the room temperature or heated up to 250 °C [ 26 , 27 , 28 ]. The substrate used in the current study is AISI 1045 that is susceptible to martensitic transformation, depending on the cooling rate [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…This selection is difficult since the mutual interaction of the various parameters is complex. Thus, it is common to apply combined parameters in the DLD process to obtain a more accurate relationship between processing parameters and the clad characteristics [33].…”
Section: Processing Effectsmentioning
confidence: 99%
“…Despite this apparent direct relation between laser power and dilution, the effect of other critical processing variables, namely the scanning speed and the feed rate, makes the establishment of relationships between processing condition and dilution complex. To overcome this difficulty, it is common to apply complex parameters, empirically adjusted, to the clad/substrate set under analysis to define the processing window [33,37,38].…”
Section: Processing Effectsmentioning
confidence: 99%
“…DED techniques have been used to successfully produce claddings and/or fully threedimensional components with different alloys, such as titanium [1,2], nickel [3,4], copper [5] and aluminium [6] alloys, tool steels [7,8] and stainless steels [9,10]. One additional material group that has been DED-processed are Maraging steels, which consist of high-strength, precipitation hardened steels.…”
Section: Introductionmentioning
confidence: 99%